Design A Quadband Frequencies Microstrip Patch Antenna With Double C-Shaped Slot - Saad, Muhammad Majdi; Husain, Mohd Nor; Hassan, Nornikman; Abd Aziz, Mohamad Zoinol Abidin; Ahmad, Badrul Hisham; Abdul Malek, Mohamed Fareq (Engg Journals Publications, 2013)
A quadband frequencies microstrip square patch antenna with double C-shaped slot at the patch is proposed in this paper. First, a rectangular shaped patch antenna is designed for 2.40 GHz frequency (WLAN application) with narrow bandwidth of 67 MHz (operate better than – 10 dB between 2.368 GHz and 2.435 GHz). Then, the double C-shaped slot had been embedded in the rectangular patch antenna. There are four stages of design (Design I, Design II, Design III and Design IV) with different dimensions of patch width and substrate width. This addition of this C-shaped slot had been producing a quadband frequency range of 2.40 GHz (2.368 GHz – 2.421 GHz), 5.0 GHz and 5.2 GHz (4.795 GHz - 5.333 GHz) and 5.6 GHz (5.521 GHz – 5.677 GHz). Parametric study with different dimension are also had been considered in Design III and Design IV.